EVAPORATION OF SINGLE CRYSTAL FORSTERITE: EVAPORATION KINETICS, MAGNESIUM ISOTOPE FRACTIONATION, AND IMPLICATIONS OF MASS-DEPENDENT ISOTOPIC FRACTIONATION OF A DIFFUSION-CONTROLLED RESERVOIR - EFFECT OF OXYGEN FUGACITY AND IMPLICATIONS FOR CREEP - Wang J.; Davis A.M.; Clayton R.N.; Hashimoto A. (My University, 1999)
Single crystals of forsterite were evaporated in a vacuum furnace at temperatures of 1500-1800°C to study evaporation kinetics, magnesium isotopic fractionation, and magnesium diffusion in forsterite. The evaporation of single crystal forsterite revealed that the evaporation process is kinetically hindered, in agreement with the results of Hashimoto (1990) on polycrystalline forsterite. The activation energy of forsterite evaporation obtained from this study is 628 kJ/mole. Forsterite can thus be much more refractory at low temperatures than expected from thermodynamic predictions.The evaporation of solid forsterite supports a model of isotopic fractionation under diffusion-controlled conditions such that isotopic fractionation during the evaporation process is restricted to the vicinity of the evaporating surface. The measured solid-gas fractionation factor of 26Mg/24Mg is smaller than the theoretical prediction, suggesting more complicated gas speciation than a monatomic Mg gas. Diffusion coefficients of forsterite at high temperature (1500-1800°C) were obtained based on measurement of isotopic profiles in the evaporation residues. Mg diffusion in forsterite along its crystallographic a-axis has a very high activation energy (608 kJ/mole).